2012
DOI: 10.2215/cjn.10401011
|View full text |Cite
|
Sign up to set email alerts
|

Informing Our Elders About Dialysis

Abstract: SummaryAs the fastest growing sector of the incident ESRD population, older patients constitute a group for which renal replacement therapy has special implications. Older CKD patients have unique needs by virtue of advanced age, high prevalence of comorbid conditions, slower progression of renal disease, and reduced survival. Burdens and risks attendant to dialysis may be amplified in the older patient and patients with impaired functional status or comorbid conditions, and therefore, dialysis may confer litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…Caring for elderly individuals with advanced CKD or end stage kidney disease (ESKD) encompasses complex medical decisions, including the choice of optimal hemodialysis (HD) vascular access (1,2). Although avoidance of tunneled central venous dialysis catheters (TCVCs) is a major goal in all HD patients, arteriovenous fistulae (AVFs) often fail to develop and/or are not used in the elderly (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Caring for elderly individuals with advanced CKD or end stage kidney disease (ESKD) encompasses complex medical decisions, including the choice of optimal hemodialysis (HD) vascular access (1,2). Although avoidance of tunneled central venous dialysis catheters (TCVCs) is a major goal in all HD patients, arteriovenous fistulae (AVFs) often fail to develop and/or are not used in the elderly (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is the extent of competing mortality higher in patients age $75 years than in younger cohorts, but also these elderly patients may have a slower rate of renal function loss from an eGFR of 15 to ,10 ml/min per 1.73 m 2 . 7,10 In a prospective followup of a cohort with a mean age of 82 years and a mean eGFR of 14 ml/min per 1.73 m 2 , Moranne et al found that 43% of these patients could postpone dialysis initiation because of stable renal function. 11 …”
Section: United States Age-and Population Growth-adjusted Rrt Incidenmentioning
confidence: 99%
“…A nondialytic approach may be associated with a better preservation of functional status and residual renal function. 5,7 Most of the elderly dialysis population dies in acute care facilities. 6 If these patients are educated about a potential for a poor life quality on dialysis and the option for an intensive conservative care management program with more quality time at home, many may choose conservative management.…”
Section: Future New Starts For Patients Age $75 Yearsmentioning
confidence: 99%
See 2 more Smart Citations